The substitution of mineral aggregates by concrete residues in asphalt pavement manufacturing (Sustainability in Debate, 2018)
Material research that is combined with sustainability principles has generated great interest due to the environmental appeal. Composites produced from civil construction waste (CCW) stand out among those materials and concrete residue represents a significant part of it. This paper presents the feasibility analysis of the use of concrete block waste replacing mineral aggregates in asphalt paving of Hot Mix Asphalt Concret (HMAC). Physical and mechanical characterization tests were performed according to the current technical standards. The results showed that composites with up to 40 % of mineral aggregate replacement by mass, satisfy the established requirements and may be used in asphalt paving.